ENERGY PROTECTORS IN TREATMENT OF ANGINA AND HEART FAILURE FOLLLOWING A LONG TERM AFTER CABG - V. E. Malikov; S. V. Rogov; L. V. Petrunina; A. S. Yusifov; E. S. Serova; G. V. Sukoyan; N. V. Karsanov (Российский кардиологический журнал)
We performed a comparative evaluation of effectiveness of Energostim and refracterin in 58 coronary patients following 5 to 7 years after CABG and/or resection of post-MI LV aneurysm in which angina at effort or rest had recurred, heart failure NYHA I-IV had developed, with atherosclerosis progressing.A 10-days course of Energostim in patients with NYHA I-II and LV EF of 45% (once the maximal effect of nifedipine, nitrates and aspirin has been reached) clearly decreases angina and heart failure severity, almost eliminates angina at rest, decreases by 50% the incidence of ST depression and results in a marked decrease of ventricular extrasystoles, accompanied by LV EF increased by 6.5% (p<0.01) and increased heart resistance to stress and improved life quality.A 10-days course of Refracterin combined with diuretics, ACE inhibitors, nitrates and aspirin, performed in 31 coronary patients with NYHA III-IV and EF<45%, decreases the functional class of angina to a greater extent than traditional treatment, promotes deremodeling and increases pump function, decreases creatinine and urea levels, as well as atherogenity index, markedly improves life quality.We therefore recommend Refracterin and Energostim as drugs of choice in the remote floow-up after CABG in patients with heart failure and arrhythmias.